EFFECT OF GOVERNANCE DIMENSIONS ON RECEIVING DONATIONS LINKED TO ENVIRONMENTAL NGOS IN BRAZIL - Lacruz, Adonai José; Nossa, Valcemiro; Guedes, Thiago de Andrade; Lemos, Katarina Rosa (Advances in Scientific and Applied Accounting, 2021)
Objective: This study aimed to analyze the effect of a set governance dimensions on donations with donor restrictions received by Non-Governmental Organizations (NGOs) in Brazil, under the agency theory perspective. Method: The study sample consisted randomly of 108 environmental NGOs operating in Brazil, and the data were obtained through document survey or direct contact. The data were analyzed using Multiple Correspondence Analysis and Multiple Linear Regression. Results: We first identify six governance dimensions (Board, Fiscal Council, Transparency, Management, Audit and Accountability) using Multiple Correspondence Analysis. We then identified through Multiple Linear Regression that four (Management, Accountability, Transparency and Audit) of the six dimensions of governance are positively associated with donations with donor restrictions. Contribuition: The findings of the study indicate that there are significant implications of the quality of governance for environmental NGO executives, for it points out that donors could make use of NGO governance information if it were better publicized.